(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
We can say that after our Independence we gained a lot of opportunities. Firstly our national and traditional values are restored and our history gained special attention. Many scientists explored about Andijan until our Independence, but this researches were only on paper or scientists did not finished their researches. After the 1990s scientists gave special attention to ancient Andijan. A lot of research projects were started to do about the history of Andijan. Scientists began to write many books, articles and pamphlets about Andijan’s history. And the most important point is that many scholars dedicated their life to learn the history of Andijan and they showed great results. Until our Independence we had a difficulty in an every branch of society. Some scientists had not finished their researches about Andijan. However after that scientists learnt about the economical changes and historical monuments in Andijan. In the 1932-1934s B.Latin made an expedition to Andijan and because of that others showed great interests in Andijan. Due to the researches of Y.A. Gulomov, M.E. Masson, A.K. Pisonchik, B.A. Abdulgoziyeva, G. Dadaboyev, R.T. Shamsiddinov, S.Jalilov, B.M. Matboboyev and other’s, many useful data were found about the history of Andijan.